Gene expression analysis of the arsC Gene involved in arsenic detoxification in Pseudomonas stutzeri and Pseudomonas putida - Hasan Abd, Ali; Abdulameer kadhim Al-ziadi, Saba ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
Arsenic bioremediation using microorganisms is an effective environmental solution for reducing heavy metal pollution, due to its high efficiency and low cost compared to traditional methods. In this study, we focused on analyzing the expression of the arsC gene, known for its vital role in reducing the highly toxic trivalent arsenic [As(III)] to its less toxic pentavalent form [As(V)], in two bacterial strains: Pseudomonas stutzeri and Pseudomonas putida. These strains were treated with escalating concentrations of sodium meta-arsenate (NaAsO₂) at 25, 50, 100, 150, and 200 ppm. Gene expression levels were measured using RT-qPCR using the ∆CT and ∆∆CT methods. The results showed that arsC gene expression gradually increased with increasing arsenic concentration in the culture medium, indicating that the strains responded to toxic stress in a regulated manner. In P. putida, fold change values ​​ranged from 9.63 at the lowest concentration to 57.47 at the highest concentration, while P. stutzeri showed a higher response, ranging from 15.71 to 85.91, respectively. Statistical analyses (ANOVA) revealed significant differences between the different concentrations (p < 0.0001), reinforcing the hypothesis that arsC gene activation is related to the severity of arsenic exposure. These results highlight the effective role of both P. putida and P. stutzeri in resisting arsenic through precise gene regulatory mechanisms. This makes them promising strains for use in bioremediation techniques for arsenic-contaminated environments and opens new avenues for employing molecular analysis to evaluate the effectiveness of microorganisms in environmental remediation. DOI: https://doi.org/10.54633/2333-024-057-008